Factors affecting calving date and its relationship with production traits of Hereford dams - Rege, J.E.O.; Famula, T.R. (1993)
Calving date (CD) records of 68896 polled Hereford dams of 120 682 calves were coded within herd-year-season with date 1 being the date the first calf was born. Factors affecting CD and its relationship with production traits were investigated. Early calving was found to be associated with high performance, conceivably because dams calving early were able to utilize the season-dependent range pastures to their advantage thus providing adequate milk supply to their calves. Weight and age of dam, weight of calf, initial CD, index of milk production potential, and previous CD were found to have significant influence on current CD. Extremely small cows at previous weaning had a tendency to calve late. Cows calving in the spring produced calves with higher overall weight per day of age than did cows calving in other seasons. Initial CD was found to affect CD in subsequent parties. Repeatability of CD was estimated at 0.23. Heritability was estimated at 0.16 (s.e.0.05) and indicated that additive genetic variance constitutes a moderate proportion of the variation in CD. Genetic correlation of CD with birth weight (-0.30), s.e. 0.10), post-weaning rate of gain (-0.64, s.e. 0.19) and yearling weight (-0.60), s.e. 0.11) indicated that `plus' additive genes for CD influenced these traits favourably. However, the corresponding correlations with pre-weaning rate of gain (-0.03, s.e. 0.08) and weaning weight (-0.05, s.e. 0.03) were not significant.